Nutritional status following One Anastomosis Gastric Bypass. Issue 2 (February 2020) - Kessler, Yafit; Adelson, Dana; Mardy-Tilbor, Limor; Ben-Porat, Tair; Szold, Amir; Goitein, David; Sakran, Nasser; Raziel, Asnat; Sherf-Dagan, Shiri
Summary: Background & aims: One Anastomosis Gastric Bypass (OAGB) has been accepted as an effective treatment for morbid obesity. However, data are scarce regarding nutritional implications of this procedure. Thus, our aim was to describe the health and nutritional status 12–20 months following OAGB surgery. Methods: A prospective cohort study on patients who underwent OAGB surgery from January 2016 to May 2017 in a large, multi-disciplinary, bariatric clinic. Pre-surgery data including demographic details, anthropometrics, co-morbidities, blood tests and lifestyle habits were obtained from the patients' medical records. Follow-up evaluations were performed 12–20 months post-surgery and data collected included anthropometrics, blood tests, eating and lifestyle parameters, adherence to follow-up regime and gastrointestinal (GI) related side effects. In addition, patients were asked to rate their overall state of health (OSH) from 0 to 100 using a visual analogue scale (VAS). Results: Eighty-six OAGB patients (72.1% women) were tested 14.7 ± 2.0 months post-operatively. Their mean age and BMI preoperatively were 46.1 ± 11.4 years and 42.0 ± 4.9 kg/m 2, respectively. The mean % excess weight loss at 12–20 months postoperatively was 88.4 ± 19.3%. Lipid and glucose profiles were significantly improved at 12–20 months postoperatively compared to baseline (P < 0.001 for all). Relatively high proportions of nutritional deficiencies were found pre-operatively and postoperatively for iron (33.9% vs. 23.7%, P = 0.238), folate (30.9% vs. 11.8%, P = 0.004), vitamin D (56.6% vs. 17.0%, P < 0.001) and hemoglobin (16.7% vs. 42.9%, P < 0.001). Postoperatively, most participants reported taking multivitamin, calcium, vitamin D and vitamin B12 supplementation (≥62.8%), having participated in at least 6 meetings with a dietitian (51.8%) and presently doing physical activity (69.4%). The mean postoperative OSH VAS score was 88.2 ± 12.3, but most participants reported on flatulence (67.4%) and some reported on diarrhea (25.6%) as GI side effects of the surgery. Conclusions: Substantial improvements in health and anthropometric parameters are found in the short-term follow-up after OAGB, with a satisfactory reported quality of life and adherence to recommendations. However, a high prevalence of some GI side effects, nutritional deficiencies and specially anemia is a matter of concern.